On a class of meromorphic functions with negative coefficients - Paskouleva, Donka (Ann. Sofia Univ. Fac. Math. and Inf., 2001)
In this paper we obtain coefficient inequalities and distortion theorems for the class T^*(α,β, A) of meromorphic functions with negative coefficients.